To Find the Frequency of Cirrhotic Cardiomyopathy in 100 patients of Chronic Liver Disease - Sohail Bashir Sulehria, M. Ahmad Khan, Anum Arooj Tariq, Abdul Wajid Khan Faisal, Mushtaq A. Shahid, Nayyer M. Elahi Afzal Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To find the frequency of cirrhotic cardiomyopathy in patients of chronic liver disease. Study design: It was a pure cross sectional type of study. Duration: After approval of synopsis, it consisted of six months i.e., from 12/04/2018 to 11/10/2018. Methods: This study was consisted of 100 patients of both sex, having age range of 16-70 years & have cirrhosis of liver assessed at least half year previously. All of them underwent transthoracic echocardiography to look for cardiomyopathy to be assessed by looking at diastolic dysfunction (i.e. increase in ratio of E/A more than 1). Each individual enrolled in current study is asked for written consent. Results: Mean age of patients was found to be 51.9±9.8 years. There were 61 males (61%) & 39 females (39%) have man to woman ratio of 1.6:1. Mean BMI was 26.5± 3.7 Kg/m2 and mean duration of cirrhosis of liver was 22.0±10.9 months. Majority (n=49) of them (49%) were of Child Pugh Class C followed by 39% of Class B & then 12% of Class A. Cardiomyopathy with cirrhosis of liver was seen in 41%. No significant difference was seen statistically in frequency of cardiomyopathy with cirrhosis of liver across all groups based on age (p value less than 0.928), sex (p value less than 0.997), BMI (p valueless than 0.983) Practical implication: If all chronic liver disease patients are screened for cardiomyopathy by echocardiography early, then we can improve quality of life for these patients & hence can survive longer. Conclusion: Cardiomyopathy associated with cirrhosis of liver was seen in a large percentage of cirrhosis liver cases and was found to be more frequent in those with more severe illness which guide us for doing transthoracic echocardiography to screen all these to timely identify and manage this complication to improve case outcome. Keywords: Cirrhosis Liver, Cardiomyopathy, Child-Pugh Class